Very small embryonic-like stem cells (VSELs) in adult mouse uterine perimetrium and myometrium - Deepa Bhartiya; Kreema James (BMC, 2017)
Abstract We have earlier reported the presence of very small embryonic-like stem cells (VSELs) in adult mouse uterus along with slightly bigger progenitors termed endometrial stem cells (EnSCs) and their regulation by ovarian hormones thus demonstrating a crucial role played by them during proliferation, differentiation and remodeling of the endometrium. Present study is a brief communication wherein we have examined the effect of higher dose of estrogen (E, 2 μg/day), progesterone (P, 1 mg/day) and follicle stimulating hormone (FSH, 5 IU/day for 5 days) specifically on the myometrium and perimetrium surrounding the endometrium in bilaterally ovariectomized mice. Similar treatment with E & P was recently used in a study published in the journal Nature to study the effect of steroid hormones on hematopoietic stem cells and this treatment regimen helps achieve hormone levels observed during pregnancy. Quiescent spherical stem cells (lacking PCNA expression) with high nucleo-cytoplasmic ratio and nuclear OCT-4A were detected in the perimetrium of atrophied (bilaterally ovariectomized) uterus. PCNA expression was observed after treatment and cells with cytoplasmic OCT-4B were invariably observed in the myometrium. VSELs were clearly visualized after treatment and the effect of P and FSH was more prominent compared to E on the development of myometrium. It is speculated that stem cells with nuclear OCT-4A located in the perimetrium differentiate to give rise to endothelial and myometrial cells with cytoplasmic OCT-4B. Based on the results of present study and published reports showing the presence of pluripotent markers (OCT-4, NANOG and SOX2) in human myometrial side population and expression of particularly OCT-4A in human leiomyomas, we speculate that these nuclear OCT-4 positive stem cells located in the perimetrium are the possible tumor initiating cells leading to the development of leiomyomas rather than the mesenchymal cells which express cytoplasmic OCT-4B.